Microbial Assessment of Selected Smoked Fishes in Akokoland, Ondo State, Nigeria - Adewole , Adeyemo M.; Balogun , Adebayo S.; Monebi , Modupe O. (African Journal of Education,Science and Technology (AJEST), 2013)
The density and diversity of microflora of cold smoked Clupea harengus and Trachurus trachurus in Akoko area of Ondo State for public health purposes were investigated. Various parts of the fish (skin, muscle, gill and intestine) were sampled for isolation and characterisation of its microbial contaminants. The results of isolation revealed the presence of Escherichia coli, Klebsiella mobilis, Serratia marcescens, Citrobacter spp, Staphylococcus aureus, Shigella spp., Bacillus cereus and Proteus vulgaris, others are Aspergillus, Rhizopus, Penicillium, Fuasrium, Neurospora spp and Candida albicans. There were observable differences in the microbial load of the different parts analysed; specifically the skin and intestine had greater microbial load. There were also differences in the range of microbial load among the local government areas studied. Akoko Northwest had the highest bacteria count of 3.90 X 106 cfu/g while the least bacteria count of 0.009 X 106 cfu/g was recorded in Akoko Southeast local government. Highest fungal count of 31 x 105 was from Akoko Northwest and the least was from Akoko Northeast. It was observed that some parts of fish had more than acceptable limit of bacteria and fungi load for wholesome food. Environmental factors could also account for differences in load and diversity but handling during sales might also have contributed. Hence, there is need for environmental health education in the area. Consumers should therefore be encouraged to soak cold smoked fishes for about 30 minutes in boiled water before consumption to minimize the risk of food poisoning.